KUALITAS AIR DI LAHAN BEKAS PENAMBANGAN NIKEL DI PULAU GEBE, MALUKU UTARA - Wibowo, Mardi (Jurnal Hidrosfir Indonesia, 2009)
Since year 1977 until 2005, PT. ANTAM has been exploited nickel ore resources at Gebe Island – Center of Halmahera District – North Maluku Province. Mining activity, beside give economically advantages also cause degradation of environment quality espicially water quality. Therefore, it need evaluation activity for change and compare of water quality at GebeIsland after mining activity. In this research we took a field survey and got 4 samples (1 samples for undisturbed water : Niwisyo Lake; 3 samples for disturbed water : Check Dam, Port and Turap Ponds). And then these samples were analyzed at BIOTROP laboratory. Base on this research, the water quality in Niwisyo Lake [only BOD parameter exceed standard] andCheck Dam were classified in Class I [only Ni concentration (0,213 mg/lt) and suspended solid (12,93mg/lt) have high value] , water in port was Class III [only DHL parameter (567 μS) has high value] and water ini Turap Ponds was Class IV [only BOD (18,43 mg/l) and DHL (497 μS) parameter have high value]. This condition may be caused the rehabilitation activity in GebeIsland has been succeded.